2004
DOI: 10.1007/s00147-004-0744-1
|View full text |Cite
|
Sign up to set email alerts
|

Written information for potential living kidney donors

Abstract: To meet the constantly growing demand for organs for transplantation the use of living related and unrelated donors continues to increase. Transplant units with a living-donor programme often provide written information to their potential kidney donors. We saw a need to assess the contents of these brochures. Written information for potential live kidney donors was requested from different Transplant units throughout the world. We obtained and analysed 16 different brochures from 14 countries. The general appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Overall, the information on financial implications, as reported by these husbands, received little attention by health care providers. Lennerling and Nyberg (2004) agree that some transplant brochures fail to mention financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the information on financial implications, as reported by these husbands, received little attention by health care providers. Lennerling and Nyberg (2004) agree that some transplant brochures fail to mention financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…Authors agree that although medical aspects of donation are usually well covered, psychosocial and financial aspects are much less frequently discussed (22,23,27). Worsened familial relations associated with live kidney donation are reported in a small number of cases and up to 25% of donors deal with adverse financial effects (28).…”
Section: Contents Of Informed Consentmentioning
confidence: 99%
“…2224 Areas that have been acknowledged as inadequate include donor reports of unexpected financial hardships related to the donation, 2225 recovery from surgery being more painful than they had anticipated, 23,24 and seeking further information regarding surgery from the Internet. This finding was consistent with results of studies of family caregivers across many types of illness.…”
Section: Living Kidney Donors and Family Caregiversmentioning
confidence: 99%
“…By using a variety of engaging and interactive methods, Internet-based resources can reach out to a more heterogeneous patient population, cross over generational barriers benefiting multiple learning styles. 22,23 However, very few studies have prospectively examined the adequacy of education for living donors and their caregivers. In an exploratory study 24 of living kidney donors, fewer than 20 participants (20%) reported that they “felt well informed.” Researchers must invest more time in developing theory-based online interventions and modes of educational delivery.…”
Section: Introductionmentioning
confidence: 99%